GAMBARAN PENGOBATAN PADA PASIEN GAGAL GINJAL KRONIK DI RUMAH SAKIT UMUM DAERAH ARIFIN AHMAD PROVINSI RIAU - Sari, Seftika; Yusuf, Muhammad (Ensiklopedia of Journal, 2024)
Chronic kidney failure is a sudden decrease in kidney function and an inability to filter and dispose of the body's electrolyte waste. The aim of this study is to look at the description of treatment for chronic kidney failure patients at the Arifin Achmad Regional General Hospital, Riau Province in 2022. The sample used in this study was chronic kidney failure patients who underwent treatment at time span January-December 2022 and has met the inclusion criteria. The samples taken in this research were 74 samples using a non-probability sampling method using purposive sampling technique. Based on research, it was found that the treatment therapy that is widely used is hemodialysis with a percentage of (94.6%). The percentage results based on the highest drug class were the gastrointestinal group at 21.7%, and based on the active drug substance, the highest active substance was omeprazole 20 mg at 19.1%.Keywords: Chronic Kidney Failure; Medication Therapy; Drug Class; Active Drug Ingredients.